Analysis of Seagrass Condition Using Spectral Reflection of Quickbird Imagery on Saronde Island North Gorontalo - Daud Yusuf; Indrawan . (Universitas Negeri Gorontalo, 2019)
This study was encouraged by the importance of understanding the conditions of seagrass which becomes the source of food for many species of marine fish. Seagrass condition will indirectly affect the quantity and quality of fish obtained by fishermen who live in coastal areas. High-resolution imagery can simplify and accelerate data collection process of conditions of seagrass on the outer islands of Gorontalo Province. This study used digital remote sensing method using unsupervised classification and also assisted by the measurements of the transcule based on the pixel size that aims to detect and to match the information obtained from QuickBird imagery, to ultimately obtain information about seagrass condition. Seagrass with abundant/good condition can be found at station 1,3,4,5, and 6 with an average cover up to 67,70%, 63,54%, 68,75%, 62,5%, and 65,62% respectively. Meanwhile, seagrass with the less abundant/poor condition can be found at station 2 with an average cover up to 50% and at station 7 with an average cover up to 52,08%. Distribution of seagrass on Saronde Island covers up to 6. 9654 Ha. Seagrass with abundant/good condition covers 4,2025 Ha, and lowly abundant/poor seagrass covers 2,7629 Ha. Seagrass on Saronde Island is still in abundant/good condition with an average cover up to 61,45 % and form mixed vegetation.